Regeneration af grundtvigianismen - Michelsen, William (Grundtvig-studier, 1984)
A Regeneration of Grundtvigianism The Vartov Book 1983 Reviewed by William Michelsen This yearbook offers a well-balanced account of Grundtvig’s influence on Danish thought right up to 1983. “ Many in the 1980s are taking courage from reading Grundtvig,” writes Birgitte Grell. He is also being used to support the theology of the women’s movement as it comes into being and to emphasize the liberating element in Luther’s preaching of the gospel, where others are emphasizing Luther’s preaching of the law. Grundtvig’s concept of “ the spirit of the people” (folkelighed) is the object of two widely differing essays, one on the basis of his poem The Spirit of the People (Folkeligheden) from 1849, the other a sharp attack on Grundtvig’s thought: unless someone has the courage to mix the gold up with copper and make it legal tender he belongs in a museum. He is also called a dreamer and a foghorn. Against this the reviewer insists that Grundtvig considered it would be an illusion to embrace the whole truth about mankind in a scientific system. His influence stemmed from his ability to arouse the imagination of others and warn against dangerous chimeras, and from his realism.In his characterization of St Luke the Evangelist, Bent Noack distinguishes between the historian and the historiographer. The reviewer believes that this distinction is also illuminating for a criticism of Grundtvig as a historian. In another article, on Danish as a subject in the comprehensive school (folkeskole), we are told that the art of story-telling has been forgotten. Grundtvig had this ability. His biblical and historical stories are re-interpretations in narrative form. This is also true of his historiography.Perhaps the most interesting is Jan Lindhardt’s article on Bible-reading, written with both gravity and humour: “ When Jesus says that “I am the way, the truth and the life” it is not a postmarked claim” . Why should we read the Bible? One way or another it must be because it is about He who is the way, the truth and the life. “ This does not mean that one must abandon the historico-critical approach, but it must be subordinated to the purpose or it will be comical and ridiculous.” This was what Luther did, as Jan Lindhardt showed in his book Martin Luther and shows again here. It was clear to Grundtvig that the Bible was superior to its reader, also as a historical source, that is, as a source for the Mosaic-Christian view and thus the Christian faith.